ANALISIS KECENDERUNGAN PENELITIAN SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERSITAS MUHAMMADIYAH SUKABUMI TAHUN AKADEMIK 2014-2015 - Muhassanah, Nur’aini; Imswatama, Aritsya (JURNAL E-DUMATH, 2016)
The purpose of this research describe the distribution and trends of theundergraduate thesis that conducted by the Mathematics Education Departmentstudents in terms of the research type, focus of the research, research materials,and research subject, and also describe the difficulties experienced by thestudents. This research is a qualitative case study. The subjects of the researchare 8 th semester of Mathematics Education Department students in the academicyear 2014-2015. The data collecting technique used questionnaire and interviewmethods. The data validity used triangulation method, coordinating betweenquestionnaire and interview data. Results of this research are: (1) the type ofstudent research is quantitative; (2) the focus of the research is learning modeland problem solving; (3) the research material is Geometri; and (4) the researchsubject is junior high school students. In addition, the results obtained thestudent difficulties in arrange the undergraduate thesis and also the solutionsare: (1) they canât organize their time, the solution make a good planning, (2) thedifficulty in finding, determine the problem, and also determine theundergraduate thesis title, the solution make an undergraduate thesis mapactivities; (3) the difficulty of processing and data analysis and also the laziness,the solution is motivate yourself; (4) The difficulty to meet the lecturers, thesolution is discuss with friends, lecturers, and also family; and (5) the difficultyduring made the instrument, the solution is looking for and reading references.Keywords: trends of the undergraduate thesis , distribution of the undergraduatethesis